Performance Evaluation of Car Cargo Scanner Systems for Determining Linear Attenuation Coefficients of Aluminum Metal Sheets: Modeling - Amir Mohammad Beigzadeh; Mojtaba Askari (مجله مدل سازی در مهندسی)
This study has investigated the performance of the car scanner cargo system in determining the linear attenuation coefficient of aluminum metal from the images obtained from a modeled car scanner imaging system. This system is based on a scintillation array detector and a radiation generator based on gamma emitter isotope. This research includes modeling the interaction of gamma radiation with the commonly used metal aluminum and analyzing the properties of its linear attenuation coefficient based on the data obtained from the scintillation detector system. For this purpose, radiographic images of aluminum sheets with different thicknesses were first extracted using modeling. Mcnpx monte Carlo code was used to model the system. The obtained images were processed using the algorithm written with MATLAB. Linear attenuation coefficient histograms were obtained from the processed images. Eight conventional functions were fitted on histogram graphs of linear attenuation coefficient. The parameters of the fitted graphs and the fitting accuracy of each were obtained and compared with each other. The average value of the calculated linear attenuation coefficient was compared with the experimental and modeling results of other researches, which showed a good agreement with each other.